Effect of selenium incorporation on the structure and in vitro bioactivity of 45S5 bioglass - Karakuzu-lkizler, Burcu; Terzioğlu, Pınar; Oduncu-Tekerek, Bilge Sema; Yucel, Sevil (Springer, 2020)
In vitro bioactivity, biodegradation, and biocompatibility behavior of a new bioactive glass systems were investigated with the incorporation of selenium oxide, for the replacement of sodium oxide in the traditional 45S5 bioglass composition. The apatite-forming ability of melt-derived bioactive glasses was evaluated by immersion studies in simulated body fluid while monitoring the concentration of silicon, calcium, phosphorus, sodium, and selenium in the medium. The weight loss of bioactive glasses and pH change in the tris-(hydroxymethyl)-amino methane buffer solution was determined to observe the biodegradation behavior of glass samples. The glasses were characterized by a Fourier transform infrared spectroscopy, scanning electron microscopy, inductively coupled plasma, and Vickers hardness measurements. The biocompatibility evaluation of the glasses was determined through in vitro osteogenesis assays by cell viability, alkaline phosphatase activity, and mineralized matrix formation. The incorporation of selenium enhanced the hydroxyapatite formation on the bioactive glass surface and microhardness of glasses. The hardness of glasses was found to decrease with immersion duration. The results indicate that selenium incorporated bioactive glasses can be used as bioactive material in bone tissue engineering applications.
Keywords: Alkaline phosphatase; Biodegradation; Hydroxyapatite; Melt-derived bioactive ceramic; Selenium